Karyotype, sex determination, and meiotic chromosome behavior in two pholcid (Araneomorphae, Pholcidae) spiders: implications for karyotype evolution. - Adriana E Golding; Leocadia V Paliulis (PLoS ONE, 2011)
There are 1,111 species of pholcid spiders, of which less than 2% have published karyotypes. Our aim in this study was to determine the karyotypes and sex determination mechanisms of two species of pholcids: Physocyclus mexicanus (Banks, 1898) and Holocnemus pluchei (Scopoli, 1763), and to observe sex chromosome behavior during meiosis. We constructed karyotypes for P. mexicanus and H. pluchei using information from both living and fixed cells. We found that P. mexicanus has a chromosome number of 2n = 15 in males and 2n = 16 in females with X0-XX sex determination, like other members of the genus Physocyclus. H. pluchei has a chromosome number of 2n = 28 in males and 2n = 28 in females with XY-XX sex determination, which is substantially different from its closest relatives. These data contribute to our knowledge of the evolution of this large and geographically ubiquitous family, and are the first evidence of XY-XX sex determination in pholcids.